Mapping the therapeutic landscape in emergency incisional hernia: a scoping review - Quiroga Centeno, Andrea; Schaaf, Sebastian; Morante-Perea, Ana Pilar; Antoniou, Stavros A.; Bougard, Heather; Bracale, Umberto; Giovannini, Sara Capoccia; Deerenberg, Eva; Fortelny, René H.; Gaarder, Christine; García-Ureña, Miguel Ángel; Gilmore, Katie; et al. (Hernia, 2025)
Purpose: Incisional hernias (IH) represent common complications following abdominal surgeries, with emergency repair associated with increased morbidity and mortality. This scoping review aimed to map the existing literature on emergency incisional hernia repair, identify research gaps, and inform future guideline development. Methods: A comprehensive literature search was conducted in PubMed MEDLINE and SCOPUS for studies published between January 2000 and August 2024. Articles addressing any aspect of emergency incisional hernia repair in adults were included. Data extraction focused on study characteristics, patient demographics, surgical approaches, and outcomes. Results: Of 801 unique articles identified, 73 met the inclusion criteria. Most were cohort studies (73.97%), with only one randomized trial. The primary areas of interest were repair methods (47.95%), operative outcomes (31.51%), risk assessment (16.44%), and diagnosis (5.48%). Pooled analysis revealed a predominantly female (63%), elderly (mean age 62.3 years), and comorbid patient population. The most frequent study endpoints were readmission (18%), surgical site infection (12%), reoperation (8%), and mortality (4%). Significant heterogeneity was observed in defect characterization and surgical techniques. Conclusion: This review highlights a paucity of randomized studies guiding emergency incisional hernia management. Key issues identified include inconsistent definitions of emergency presentation, limited data on hernia characteristics, and a lack of standardized outcome reporting. Future research should focus on developing a unified classification system for emergency incisional hernias, evaluating the role of imaging in decision-making, and conducting comparative studies on various treatment strategies across different clinical scenarios.